2017
DOI: 10.1016/j.celrep.2017.05.076
|View full text |Cite
|
Sign up to set email alerts
|

A Tonoplast P3B-ATPase Mediates Fusion of Two Types of Vacuoles in Petal Cells

Abstract: It is known that plant cells can contain multiple distinct vacuoles; however, the abundance of multivacuolar cells and the mechanisms underlying vacuolar differentiation and communication among different types of vacuoles remain unknown. PH1 and PH5 are tonoplast P-ATPases that form a heteromeric pump that hyper-acidifies the central vacuole (CV) of epidermal cells in petunia petals. Here, we show that the sorting of this pump and other vacuolar proteins to the CV involves transit through small vacuoles: vacuo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 45 publications
3
38
0
Order By: Relevance
“…The tannin‐related genes ANR and LAR were not affected by ASRs M1 overexpression, indicating that these MYBs are specific for the anthocyanin pathway. Similarly, no expression of the flavonol synthase gene ( FLS) was induced in ASRs‐ OE lines, and no induction was observed for the expression of PH1 and PH5 , the two P‐ATPases required for vacuolar hyperacidification in the epidermis of petals (Faraco et al., , ; Quattrocchio et al., ; Verweij et al., ), consistent with the pH values measured in petals.…”
Section: Resultssupporting
confidence: 56%
“…The tannin‐related genes ANR and LAR were not affected by ASRs M1 overexpression, indicating that these MYBs are specific for the anthocyanin pathway. Similarly, no expression of the flavonol synthase gene ( FLS) was induced in ASRs‐ OE lines, and no induction was observed for the expression of PH1 and PH5 , the two P‐ATPases required for vacuolar hyperacidification in the epidermis of petals (Faraco et al., , ; Quattrocchio et al., ; Verweij et al., ), consistent with the pH values measured in petals.…”
Section: Resultssupporting
confidence: 56%
“…Interestingly, a proteomics screen for the Arabidopsis SYP132 interactome has identified the H + -ATPase proteins as one of the SNARE binding partners (Fujiwara et al, 2014). Indeed, some interesting interactions of trafficking SNAREs with non-SNARE proteins are noted to affect cellular traffic and plant physiology (Honsbein et al, 2009;Faraco et al, 2017;Barozzi et al, 2019). We are currently investigating the dynamics of SYP132 interactions and their relationship to H + -ATPase traffic as well as the physiology of plant growth.…”
Section: Resultsmentioning
confidence: 99%
“…Two KCO channels ( VIT_12s0028g00140 and VIT_12s0028g00130 ) are also among the identified targets. Most TPK/KCO proteins localize on the tonoplast (Voelker et al ., ; Faraco et al ., ; Appelhagen et al ., ) and in petunia epidermal petal cells are trafficked to the central vacuole via additional vacuoles, known as vacuolinos, the genesis of which are dependent on PH3 and PH4 (Faraco et al ., ). It is possible that a similar subcellular route is taken by their grapevine counterparts; the identification of putative MBWW target genes encoding proteins involved in membrane recognition, fusion and remodelling, as a RabGAP/TBC ( VIT_11s0016g05350 ) domain protein and three patatin‐like phospholipases ( VIT_18s0001g10900 ; VIT_18s0001g10830 and VIT_18s0001g10870 ), strongly suggested that vacuolar trafficking in grapevine is under the same type of regulation as in petunia.…”
Section: Discussionmentioning
confidence: 97%